The shelf life of coarse beef sausage using dawadawa (Parkia biglobosa) pulp powder as an extender - Herman, Richard Ansah Herman; Adzitey, Frederick; Teye, Gabriel Ayum (Journal of Postharvest Technology, 2024)
The shelf life and sensory characteristics of coarse beef sausage with dawadawa (Parkia biglobosa) pulp powder (DPP) as an extender were investigated. The sausages were formulated in four treatments with one serving as a control and the dawadawa pulp powder was added to the other three at various inclusion levels of 35g, 40g and 45g in T2, T3 and T4 respectively. The beef sausages were spiced and stuffed in natural casings and stored at a temperature of 4°C for 14 days. Weekly sensory characteristics of the products were evaluated for texture, taste, color, flavor, cohesiveness, juiciness and overall liking over a period of two weeks after storage. There were significant differences (P < 0.001) in the taste, flavor and overall liking of the product. All other parameters were not significantly different (P > 0.05). Microbial load analysis of the beef sausage was carried out weekly for the 14 days of storage. The highest microbial load count was obtained in T3 on day 7 with 5.18×106cfu/g and the lowest count in T2 on day 14 with 1.63×105cfu/g even though the difference was not significant. The dawadawa pulp powder did not reduce the microbial load of the beef sausage and hence the shelf life of the products was not extended.